2005
DOI: 10.4049/jimmunol.175.12.8181
|View full text |Cite
|
Sign up to set email alerts
|

Activated Macrophages Infected with Legionella Inhibit T Cells by Means of MyD88-Dependent Production of Prostaglandins

Abstract: To understand how macrophages (Mφ) activated with IFN-γ modulate the adaptive immune response to intracellular pathogens, the interaction of IFN-γ-treated bone marrow-derived murine Mφ (BMφ) with Legionella pneumophila was investigated. Although Legionella was able to evade phagosome lysosome fusion initially, and was capable of de novo protein synthesis within IFN-γ-treated BMφ, intracellular growth of Legionella was restricted. It was determined that activated BMφ infected with Legionella suppressed IFN-γ pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Several TLRs are important for host responses against Legionella infection. Specifically, TLR2 is required for murine macrophage cytokine and prostaglandin responses to purified L. pneumophila lipid A and intact L. pneumophila (33). It has been shown that the L. pneumophila flagellin protein activated TLR5, and polymorphisms of TLR5 in humans have been linked to enhanced susceptibility to Legionnaires' disease (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Several TLRs are important for host responses against Legionella infection. Specifically, TLR2 is required for murine macrophage cytokine and prostaglandin responses to purified L. pneumophila lipid A and intact L. pneumophila (33). It has been shown that the L. pneumophila flagellin protein activated TLR5, and polymorphisms of TLR5 in humans have been linked to enhanced susceptibility to Legionnaires' disease (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in vitro, wild-type Lpn replicate efficiently within (50-to 100-fold increase in Lpn CFU in 24 h) and eventually lyse macrophages (48). It has been shown in vitro that if macrophages are activated by pretreatment with exogenous IFN-␥, Lpn fails to replicate in these cells (47,49,50). The action of IFN-␥ arms the macrophages to avoid establishment of the replication-competent vacuole, such that the Lpn-containing phagosomes mature along the default pathway into phagolysosomes, thereby blocking Lpn replication and eventually killing the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…To block PGE 2 production, the T cells were cultured in the presence of 1 M indomethacin (an inhibitor of both cyclooxygenase-1 and -2; Cayman Chemicals) as previously described (29,30). Where noted, a Transwell with 0.4-m pore polycarbonate membrane insert (Corning Life Sciences; Costar) was used to separate S. Typhimurium from the T cells, and a polyethersulfone membrane with 0.2-m pore (Nalgene) was used to obtain T cell culture supernatant.…”
Section: T Cell Enrichment and Assaymentioning
confidence: 99%